El abordaje de la prensa escrita sobre el femicidio en Costa Rica en el 2006 - Solano Ramírez, Laura Vanessa (2007)
UCR::Docencia::Ciencias Sociales::Facultad de Ciencias Sociales::Escuela de Sociología